LEGAL REGULATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGY: PROBLEMS OF THEORY AND PRACTICE - Diduk, Alla; Lytvyn, Stepan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of this article is to study the current problematic issues of theory and practice relating to legal regulation of artificial intelligence technology. For this purpose, the author analyzes the concepts of “digital technologies”, “artificial intelligence”, “legal regime of artificial intelligence”, and “legal personality” of artificial intelligence. The analysis also examines the peculiarities of the legal regime of artificial intelligence technologies and their practical significance. The methodological basis of the study is general scientific and special methods of scientific knowledge. The use of these methods made it possible to analyze the peculiarities of legal regulation of artificial intelligence technologies and to describe the problems of its legal regime. Results: artificial intelligence technologies require comprehensive legal regulation that will establish clear boundaries for their use and introduce effective control mechanisms; formulation of proposals for improving the current civil legislation of Ukraine, taking into account global trends in the legal regulation of artificial intelligence; implementation of international experience and development of special legislation will ensure a balance between technological progress and protection of citizens’ rights. Discussion: the rapid development of artificial intelligence is accompanied by a number of potential threats to participants in civil legal relations, including the provision of false information, failure to fulfill contractual obligations, health hazards, violation of the right to a fair trial, and overloading of the judicial system. Of particular concern is the use of artificial intelligence in areas that directly affect human rights, such as medicine and the judiciary. Algorithmic errors can lead to negative consequences, including violations of human rights and legal liability for damages. Also, automation of judicial processes cannot replace the human factor, as artificial intelligence does not have the moral principles and professional ethics necessary for the administration of justice.